Buried deep beyond the veil of extinction: Euphyllophyte relationships at the base of the spermatophyte clade. Issue 8 (12th June 2018) - Toledo, Selin; Bippus, Alexander C.; Tomescu, Alexandru M. F.
Abstract : Premise of the Study: The deep origin and early evolution of seed plants (spermatophytes) are poorly understood. Starting in the Early Devonian, euphyllophytes diversified rapidly into several groups. Two of these groups, progymnospems and Stenokoleales, along with satellite taxa, have been involved in discussions of seed plant origins. Because these early lineages are extinct, the key to the origin and early evolution of seed plants lies in the fossil record. Decades‐long paleobotanical work has produced data on the diversity and anatomy of fossil species, which now provide a foundation for exploring seed plant origins in a phylogenetic context. Methods: We address phylogenetic relationships between early seed plants, aneurophytalean progymnosperms, Stenokoleales, and several Devonian species of uncertain affinities using parsimony analyses that include 28 anatomically preserved species (the most comprehensive taxon sampling to date) and 49 morphoanatomical characters (including nine continuous characters). Key Results: Our analyses recover monophyletic seed plants, Stenokoleales, and aneurophytes, with the latter placed as sister to a clade (termed the bilateral clade) that includes the former two. When added in the analysis, continuous characters based on anatomy improve phylogenetic resolution. Conclusions: Our results support the groups defined by traditional taxonomy, resolve Stenokoleales nested among the lignophytes, and indicate that seed plants may share a closer ancestor with Stenokoleales than with aneurophytes. Additionally, our trees suggest a Givetian minimum age for the seed plant ancestor, a late Emsian minimum age for the Stenokoleales, and early Emsian minimum ages for lignophytes, the bilateral clade, and the aneurophyte ancestor.